Three panoramic indices for identification of healthy older people at a high risk of osteoporosis - Bramma Kiswanjaya; Menik Priaminiarti; Hanna H Bachtiar-Iskandar (Saudi Dental Journal, 2022)
Background: This study aimed to identify whether healthy older adults are at a high risk of osteoporosis based on the association between the T-score values of bone mineral density (BMD) and three panoramic indices. Materials and methods: All participants (50–64 years old) underwent calcaneal quantitative ultrasound (QUS) bone densitometry. In total, 371 panoramic images were included in the analysis. The mandibular cortical width (MCW), mandibular cortical index (MCI), and panoramic mandibular index (PMI) were the three parameters assessed. The data were examined using one-way analysis of variance or Kruskal–Wallis H and post hoc tests. Spearman’s rho was used to measure correlation coefficients. Results: T-score distributions in the normal, osteopenia, and osteoporosis categories were 80 (21.6%), 236 (63.6%), and 55 (14.8%), respectively. T-scores were significantly related to age, MCW, PMI, and MCI (p < 0.001). Participants with osteopenia and a risk of progression to osteoporosis had an average MCW value of < 3.38 mm, a PMI of < 0.31, and an MCI class 2 and 3 distribution in 211 (56.9%) participants. The highest to lowest correlation coefficients with a significant relationship to the T-score were for age (r = -0.844), MCI (r = 0.456), MCW (r = 0.359), sex (r = 0.354), and PMI value (r = 0.292). Conclusions: This study found that healthy older people with Class 3 MCI, an MCW < 3 mm, and a PMI ratio < 0.3 had a significant association with lower BMD T-scores on QUS and were at higher risk of osteoporosis.